2003
DOI: 10.1002/jbt.10071
|View full text |Cite
|
Sign up to set email alerts
|

Changes in expression and activity of glutathione S‐transferase in different organs of schistosoma haematobium‐infected hamster

Abstract: Schistosomiasis is a major health problem in many subtropical developing countries, causing a number of serious pathologies, including bladder cancer. Most of the toxic compounds formed as a result of these infestations are derived either exogenously or formed endogenously and can be conjugated with glutathione (GSH) via glutathione S-transferase (GST). The present study investigates the effect of Schistosma haematobium infection on the activity of GST and glutathione reductase (GR) and levels of glutathione a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…An alternative explanation could be an increase in extracellular levels of glutamate which, in turn, might inhibit the uptake of cystine via the glutamate-cystine exchange system, thereby reducing GSH synthesis. Our result are in line with the results previously reported by Sheweita et al (2003) who observed a depletion of GSH level in kidney and bladder by 72 and 54 % at 8 and Results were expressed as mean ± SE and significant difference according to control group at p B 0.05. ANOVA showed a highly significant difference between all groups at p B 0.0001 ** p B 0.01 highly significant difference compared to control a p B 0.05 significant difference compared to S. haematobium 10 weeks post-infected with S. haematobium.…”
Section: Discussionsupporting
confidence: 93%
“…An alternative explanation could be an increase in extracellular levels of glutamate which, in turn, might inhibit the uptake of cystine via the glutamate-cystine exchange system, thereby reducing GSH synthesis. Our result are in line with the results previously reported by Sheweita et al (2003) who observed a depletion of GSH level in kidney and bladder by 72 and 54 % at 8 and Results were expressed as mean ± SE and significant difference according to control group at p B 0.05. ANOVA showed a highly significant difference between all groups at p B 0.0001 ** p B 0.01 highly significant difference compared to control a p B 0.05 significant difference compared to S. haematobium 10 weeks post-infected with S. haematobium.…”
Section: Discussionsupporting
confidence: 93%
“…The expression of GST isoenzymes was reduced in the kidney and bladder tissues at later stages (8 and 10 weeks) of the infection, and reduced in spleen and liver tissues at all infection stages. Free radicals (measured as thiobarbituric acid reactive substances) increased to high levels in the bladder, and to a lesser extent in other organs (Sheweita et al, 2003). [The Working Group noted that the number of animals in the S. haematobium and the control groups was unspecified.…”
Section: (B) Inhibition Of Glutathione-s-transferase (Gst) Activity I...mentioning
confidence: 99%
“…El-Rigal et al (2011) suggested that the intensified production of superoxide radicals by the macrophages of liver granulomas in S. mansoni infection might be the reason for the heightened MDA levels. Meanwhile, using hamster models of S. hematobium infection, (Sheweita et al, 2003) indicated that glutathione levels were reduced while lipid peroxides were elevated in various hamster organs, suggesting that organs become damaged in the presence of heightened levels of free radicals.…”
Section: Discussionmentioning
confidence: 99%